Hydrochemical Assessment of Groundwater and Some Springs in Qazaniyah Area, Diyala province, East of Iraq - Fakhre , Haider N.; Abdulhussein, Firas Mudhafar (Iraqi Journal of Science, 2020)
The Qazaniyah study included the analysis of 18 wells and 2 springs for the dry period in October 2018 and the wet period in April 2019, including the analysis of physical and chemical properties and the study of heavy elements (Fe, Zn, Cd, Pb, Ni and Cu).The results showed that the water wells and springs for the two periods are highly mineralized and characterized by low alkalinity and very high hardness. Water was fresh in some wells and salty in the others, whereas it was fresh in the springs. Most of the wells had sodium chloride type, except the wells 12, 7, 6, and 5 which were of Calcium chloride type. The springs for both seasons had calcium chloride type. Based on the World Health Organization criteria , all the wells for both periods are not suitable for human drinking, whereas the springs are suitable only for drinking of livestock and poultry. Sodium adsorption rate (SAR) was excellent for groundwater and springs for both seasons. The percentage of sodium (na%) in both seasons showed that the wells 18,17,15,11,4,3 as well as the springs are within the permissible limits for irrigation purposes, while the remaining of the wells was not.